2019
DOI: 10.1097/mlr.0000000000001005
|View full text |Cite
|
Sign up to set email alerts
|

National Testing of the Emergency Department Patient Experience of Care Discharged to Community Survey and Implications for Adjustment in Scoring

Abstract: Background: The emergency department (ED) setting is unique and measuring quality of care in the ED requires the development of ED-specific tools. The Emergency Department Patient Experience of Care Discharged to Community Survey was designed to measure patient experience in the ED setting. Objectives: Describe results from the Emergency Department Patient Experience of Care Discharged to Community Survey including respondent characteristics and reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Given the overall low response rates in this population, the issue of nonresponse bias is important to consider. Previous work in the ED has shown that older patients and female patients are generally more likely to respond (Parast et al 2019). In our study, we found that when comparing the two best performing modes (two-stage and three-stage SMM), the likelihood of response was similar between the two modes regardless of age or gender.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Given the overall low response rates in this population, the issue of nonresponse bias is important to consider. Previous work in the ED has shown that older patients and female patients are generally more likely to respond (Parast et al 2019). In our study, we found that when comparing the two best performing modes (two-stage and three-stage SMM), the likelihood of response was similar between the two modes regardless of age or gender.…”
Section: Discussionsupporting
confidence: 61%
“…One recent survey of ED patients in 50 hospitals obtained low response rates (14%-22%) for single-mode mail-only and telephone-only administration but a higher response rate (29%) for a two-stage sequential mixed mode (SMM) of a mailed survey with telephone follow-up (Parast et al 2019). Other work has tested nontraditional modes in the ED setting, including on-site electronictablet-based survey administration to assess patient experience (The Beryl Institute 2012).…”
mentioning
confidence: 99%
“…Details regarding the survey instrument, study design, sampling, and item scoring are available elsewhere. 5,6 Our analytic sample included 3122 eligible survey respondents from 50 hospitals. Gender was characterized as male vs. female and obtained from hospital administrative data.…”
Section: Methodsmentioning
confidence: 99%
“…Given that these survey results inform evaluations of provider performance, it is essential that they accurately reflect the experiences of the patient population by having a reasonably high survey response rate, obtaining a representative sample of respondents, and utilizing statistical methods to ensure representative and unbiased results. In this paper, we examine a patient experience survey of hospital-based emergency department (ED) patients discharged to home after their ED visit (rather than admitted to the hospital), referred to as discharged-to-community (Parast et al 2019) patients. As previous studies have found very low survey response rates among such patients, less than 20% (Mathews et al 2019;Weinick et al 2014), we sought to understand how response rates could be improved in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in the ED DTC population has shown that single-mode protocols, such as mail-only or web-only, and distribution within the ED do not perform well (1-14% response rate), but sequential mixed-mode approaches may have promise (Mathews et al 2019;Parast et al 2019). In this paper, we describe results from a randomized test of nine experimental survey administration protocols, eight of which began with an invitation to a web survey, then followed by a mailed survey, a telephone survey or both.…”
Section: Introductionmentioning
confidence: 99%